Drying Behavior and Effect of Drying Temperatures on Cyanide, Bioactive Compounds, and Quality of Dried Cassava Leaves - Sawittree Chaiareekitwat; Marcus Nagle; Busarakorn Mahayothee; Pramote Khuwijitjaru; Parika Rungpichayapichet; Sajid Latif; Joachim Müller (Applied Sciences)
In this study, the drying behavior and quality of the dried leaves of cassava (Manihot esculenta Crantz) of the ‘Rayong 5’ cultivar from Thailand were investigated. An increase in the drying temperature resulted in an increased drying rate and a reduction in drying time. The Page model provided the best fit for describing the drying characteristics of cassava leaves, with the entire drying process occurring in the falling rate period. The results showed that cyanide content was sensitive to high temperatures, with drying at 80 °C being the most effective method for toxin elimination. Prolonged drying periods lead to the degradation of vitamin C. Drying cassava leaves at 50–80 °C did not significantly affect β–carotene levels. However, lutein, chlorophyll–a, and chlorophyll–b were reduced after drying. The drying processes did not change the crude proteins content but increased the levels of histidine, alanine, and aspartic acid. In this study, high-temperature, short-time drying was identified as the optimal condition for detoxification, maintaining nutrients, and preserving the color of dried cassava leaves.